From the Editors - Yunisrina Qismullah Yusuf (Universitas Syiah Kuala, 2015)
This is the front matter of Studies in English Language and Education Volume 2 Number 1 (2015), which includes: • Cover • About the Journal • Editorial Team • Table of Contents